Scientific Elites’ Attitude to Future Career in Iran and Its Effect on Tendency to Migration - mahsa sadeghinezhad; mohammad mazloum khorasani (توسعه اجتماعی, 2018)
The scientific elites are bases of development of societies. The results of less attention to them are coefficient of intelligence crisis and damage to development process in different aspects. Purpose of this paper is investigation of scientific elites’ attitude to future career in Iran and its effect on tendency to migration. Research method is survey and universe was elite students of ferdowsi university of Mashhad and research sample was selected with method of stratified sampling with optimum allocation. Data was collected with questionnaire and analyzed with Spss and Amos softwares. Validity and reliability of questionnaire is determined via face validity and coefficient of Cronbach’s alpha (0.74). The results show that elite students’ attitude to future career in Iran was negative and this attitude was more intense in men. Dimensions of attitude to future career (i.e., satisfying material, intellectual, spiritual needs and proportion of job with field) and experience of migration have direct and significant effect on tendency to migration. Dimension of satisfying material needs via affecting two dimension of satisfying intellectual, spiritual needs has indirect and significant effect on tendency to migration. While, gender doesn’t have any significant effect on it.